Running status and history: A self-report study. (September 2019) - Wiegand, Kristyne; Mercer, John A.; Navalta, James W.; Pharr, Jennifer; Tandy, Richard; Freedman Silvernail, Julia
Abstract: Objectives: The purpose of the current study was to compare injury and running history among current and former runners who consider themselves either injured or uninjured. Design: Cross-sectional survey. Setting: Online survey, available to any individuals over the age of 18 who currently run (runners) or who once ran regularly but are no longer running (former runners). Participants: 312 participants (age 38 ± 12 years, 219 males, 89 females, 4 did not disclose) completed the survey. Main outcome measures: This study assessed injury incidence, consequences of injury such as time off, and reported injury diagnoses and treatments. Chi-square and frequency analyses were calculated to describe running status, injury counts, and response to injury. Results: Most participants (80%) reported 1 + running injury. 775 total injuries were reported. The four most common injuries were iliotibial band syndrome (34%), plantar fasciitis (30%), strained thigh/hip muscle (25%), and medial tibial stress syndrome (22%). About 40% of participants continued to run with these injuries. Conclusions: Injury frequencies (80%) agreed with those reported in the literature. The results of this study also support the notion that running injuries exist on a continuum of severity and that the individual response to injury is complex and determined by various factors. Highlights: 80% of runners surveyed reported experiencing at least one running injury. Half of the individuals who reported no running injuries, did report pain while running. The two most common injuries reported were iliotibial band syndrome and plantar fasciitis. Many runners continued to run while injured and did not seek medical care.